Responsiveness, support, and responsibility: How democratic responsiveness facilitates responsible government. (May 2020) - Linde, Jonas; Peters, Yvette
Representative democracy entails governments that are both responsive and responsible. Mair argued that political parties find it increasingly difficult to balance these two tasks. With an increase in international commitments and interdependence, governments cannot always follow the wishes of their citizens but need to be responsible instead. Our study examines the responsiveness–responsibility link from the angle of citizen perceptions. We argue that when governments are seen as responsive they build a "buffer" of support, allowing them to make decisions that are not necessarily responsive but possibly responsible. By being responsive, governments build a reservoir of goodwill, which they can use to survive more difficult periods. Using data from the 2012 European Social Survey, we test whether perceived responsiveness feeds into this reservoir and whether this reservoir consequently increases perceived responsibility. We find support for this link, suggesting that responsiveness and responsibility do not need to be trade-offs but can complement each other.